Bidirectional effects of voluntary exercise on the expression of Bdnf isoforms in the hippocampus of Hatano rat strains displaying different activity levels - Shuichi Chiba; Hikaru Asano; Shogo Moriya; Taichi Hatakeyama; Shohei Kobayashi; Ryo Ohta; Maiko Kawaguchi (Wiley, 2023)
Abstract Brain‐derived neurotrophic factor has functional mRNA isoforms, whose expression is assumed to mediate the beneficial effects of exercise in neuropsychiatric disorders. This study aims to reveal the mechanism of intensity‐dependent effects of voluntary exercise, focusing on the expression of Bdnf mRNA isoforms in Hatano rats. Animals with different voluntary activity were housed in cages with a locked or unlocked wheel for 5 weeks. The expression levels of Bdnf isoforms and the corresponding coding sequences (CDS) were measured in the hippocampus using real‐time polymerase chain reaction (PCR). We found that exercise increased the expression of Bdnf isoform containing exon 1 in the high‐intensity‐running strain and decreased the expressions of Bdnf exon 1, 3, 6, 7, 8, and 9a in mild‐intensity‐running animal. The expression of Bdnf CDS was increased by exercise in both strains. These results suggest that expressions of Bdnf isoforms depend on the intensities of voluntary exercise, but the involvement of subjects' genetic background could not be excluded. Our finding also implies that the bidirectional effects of exercise may not be mediated via the final product of Bdnf.